Impact of Online Learning On The Personal Development of Students - Anik Mufarrihah; Sukmawati Sukmawati; Susanti Susanti; Karmila P. Lamadang (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Online learning has an impact on student development from the aspect of learning enthusiasm, values and even student personality. This is because the learning climate does not support the student learning environment. Online learning can result in students not being able to meet many people and prevent students from being able to directly relate to their friends at school. In this study, an attempt was made to determine the impact of online learning on student personality development. The purpose of this research is to find out how effective the learning process and the use of online learning methods are, so that students still feel happy rather than bored. This research was conducted by reviewing several case studies from several journals and scientific research references.